Second Law Analysis for Couple Stress Fluid Flow through a Porous Medium with Constant Heat Flux - Samuel Olumide Adesanya; Michael Bamidele Fakoya (Entropy, 2017)
In the present work, entropy generation in the flow and heat transfer of couple stress fluid through an infinite inclined channel embedded in a saturated porous medium is presented. Due to the channel geometry, the asymmetrical slip conditions are imposed on the channel walls. The upper wall of the channel is subjected to a constant heat flux while the lower wall is insulated. The equations governing the fluid flow are formulated, non-dimensionalized and solved by using the Adomian decomposition method. The Adomian series solutions for the velocity and temperature fields are then used to compute the entropy generation rate and inherent heat irreversibility in the flow domain. The effects of various fluid parameters are presented graphically and discussed extensively.